Giant Cells of Escherichia coli - Adler, Howard I. (1968)
A mutant strain of Escherichia coli K-12 produced amorphous cells when grown in a variety of media. The lon(−) allele, known to increase the radiation sensitivity of the cytokinesis mechanism, was introduced into the mutant by means of conjugation. Cells of this recombinant strain grew, after exposure to radiation, into giant amorphous cells, approximately 500 to 1,000 times the volume of a normal E. coli cell. These giant cells are analogous to the filaments formed after the irradiation of lon(−) rod-shaped cells.